The Faktor Determinan Terjadinya Pencabulan dan Pelecehan terhadap Perempuan - Ciek Julyati Hisyam; Benedictus Raditya; Hernan Solari; Ilham Danu Prasetyo; Muhammad Fauzil Adhim; Nasrani Nofati Waruwu; Roberto Dowansiba (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Abstract. Sexual assault and harassment against women are forms of gender-based violence that have become serious issues in various countries, both developing and developed. This problem involves not only individual aspects but also results from discriminatory social norms that place women in subordinate positions. Social stigma often serves as a barrier for victims to report incidents, while patriarchal culture exacerbates gender injustice. The psychological impact on victims is significant, causing trauma that disrupts mental health. Women's financial dependence also contributes to the difficulty of fighting violence, perpetuating this cycle. Additionally, the development of technology and social media has created new forms of harassment, such as cyber harassment, which are becoming increasingly complex. A lack of digital literacy makes women vulnerable targets. Therefore, there is a need for an approach that integrates education, legal reform, and social support to address this issue. Efforts to empower women and prevent gender-based violence must be designed to involve all layers of society and address the root causes of gender inequality.